Accuracy of Components of the SCAT5 and ChildSCAT5 to Identify Children with Concussion - Babl, Franz E.; Anderson, Vicki; Rausa, Vanessa C.; Anderson, Nicholas; Pugh, Remy; Chau, Tracey; Clarke, Cathriona; Fabiano, Fabian; Fan, Feiven; Hearps, Stephen; Parkin, Georgia; Takagi, Michael; Davis, Gavin (International Journal of Sports Medicine, 2021)
The Sport Concussion Assessment Tool 5th Edition (SCAT5) is a standardized measure of concussion. In this prospective observational study, the ability of the SCAT5 and ChildSCAT5 to differentiate between children with and without a concussion was examined. Concussed children (n=91) and controls (n=106) were recruited from an emergency department in three equal-sized age bands (5–8/9–12/13–16 years). Analysis of covariance models (adjusting for participant age) were used to analyze group differences on components of the SCAT5. On the SCAT5 and ChildSCAT5, respectively, youth with concussion reported a greater number (d=1.47; d=0.52) and severity (d=1.27; d=0.72) of symptoms than controls (all p<0.001). ChildSCAT5 parent-rated number (d=0.98) and severity (d=1.04) of symptoms were greater for the concussion group (all p<0.001). Acceptable levels of between-group discrimination were identified for SCAT5 symptom number (AUC=0.86) and severity (AUC=0.84) and ChildSCAT5 parent-rated symptom number (AUC=0.76) and severity (AUC=0.78). Our findings support the utility of the SCAT5 and ChildSCAT5 to accurately distinguish between children with and without a concussion.
Keywords: pediatric; concussion; assessment; diagnosis